Más allá del Control Room de Arbey Road: Análisis técnico de la sonoridad de los Beatles en su discografía entre 1966 y 1970 - Samaniego Vásconez, Mauricio Andrés (2016)
John Lennon, Paul McCartney, George Harrison and Ringo Starr conformed The Beatles. According to Rolling Stone magazine, The Beatles were the most important and influencial band of the 20th Century. The quartet from Liverpool grew rapidly at the beginning of the1960s and in 1964 they reached for the first time the top of UK music charts. These events made possible for one of the biggest cultural phenomenons of the 20th century to take place, Beatlemania, a whole generation of teenagers, crazed and mesmerized by the young english band. This way, the Fab Four as they were known popularly, changed music and western pop culture forever. (Leopold, 2004, par. #3; Simon and Schuster, 2001, par. 1; Simon and Schuster, 2001, par. 10; Taylor, 2014, par. 1). This project pretends to understand the technical aspects of the following Beatles albums from 1966 until 1970, the recording and post-production techniques developed in these times to recreate their sonority. It is important to clarify that the term “sonority” refers to the sound design based on the knowledge and understanding of the signal flow of electroacoustic transducers. This investigation is focused specifically on sound innovations executed and developed on these albums. The final product will be an EP containing 6 original songs influenced by the sound of The Beatles from their albums recorded between the years of 1966 and 1970. The following albums are: Revolver, Sgt. Peppers lonely hearts club band, Magical mystery tour, White album, Abbey road and Let it be. This group of songs will be recorded with recording techniques that were applied on these records but using mainly digital software and processing. The project will get started by analyzing the historical context, the recording space and studio, and the study of alternative and standard recording techniques including sound innovations. Books, articles, interviews, magazines and documentaries will be used as resources for the research needed to complete this project. This investigation is about musical production.